2018
DOI: 10.2754/avb201887010027
|View full text |Cite
|
Sign up to set email alerts
|

Detection and molecular characterization of equine herpesviruses 1, 2, and 5 in horses in the Republic of Serbia

Abstract: The presence of equine herpesviruses 1, 2 and 5 (EHV-1, EHV-2 and EHV-5) was examined in 66 samples of spinal cord, submandibular lymph nodes and spleen of healthy, non-vaccinated abattoir horses from different locations in the Republic of Serbia. Virus isolation was conducted on RK-13 cell line with the confirmation of isolated viral strains by multiplex nested polymerase chain reaction. The cytopathic effect was observed 48–72 h after the first inoculation in 28 (42.4%) organ samples, and after 5 days in 11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Analysis of the results obtained from EHVs cases outlines that EHV-1 is the most prevalent type detected, with an overall percentage of 62%. This correlates with other studies done in Egypt (64%) 24 and the Republic of Serbia (59.1%), 25 but relatively higher than the findings in Ethiopia (7.5%) 18 and Algeria (2%). 26 In the current study, identification of EHV-2 in 53% equids with signs of respiratory disease is relatively higher than other studies reported around the world.…”
Section: Discussionsupporting
confidence: 90%
“…Analysis of the results obtained from EHVs cases outlines that EHV-1 is the most prevalent type detected, with an overall percentage of 62%. This correlates with other studies done in Egypt (64%) 24 and the Republic of Serbia (59.1%), 25 but relatively higher than the findings in Ethiopia (7.5%) 18 and Algeria (2%). 26 In the current study, identification of EHV-2 in 53% equids with signs of respiratory disease is relatively higher than other studies reported around the world.…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, most of these studies were being conducted through targeting the gB gene. The genetic heterogeneity in this gene has been revealed by some researchers like Lee and Lee; Radalj et al; Ataseven et al (7,36,37). This genetic polymorphism was found in a low level though.…”
Section: Discussionmentioning
confidence: 89%
“… Balasuriya et al (2015 ) and Radalj et al (2018 ) documented that the molecular methods have advantages of rapidity and accuracy in detection and identification of EHV nucleic acid in clinical samples in compared to the traditional methods such as virus isolation, immunohistochemical, and direct immunofluorescence method. Furthermore, standard virological methods are often very laborious and time-consuming which sheds the light on the requirement for the application of nucleic acid amplification-based detection techniques, such as consensus PCR, which has already been applied in this current study, as a screening assay for EHV, while Conventional PCR was used for EHV typing.…”
Section: Discussionmentioning
confidence: 99%